Pengembangan Media SURIA (Sunda Ceria) dalam Meningkatkan Kosakata Bahasa Sunda Anak Usia 5-6 Tahun - Purwati, Dewi Ratna; Dewi, Ajeng Rahayu Tresna (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2025)
This research aims to develop an effective learning medium called SURIA (Sunda Ceria) to improve the Sundanese vocabulary skills of children aged 5–6 years. The background of this study is based on the low mastery of Sundanese vocabulary among young children and the lack of engaging and developmentally appropriate learning media. The research employed the Research and Development (R&D) method using a simplified version of the Borg and Gall model, which includes six stages as adapted from Sugiyono: identifying potential and problems, data collection, product design, validation, revision, and product testing. Data collection techniques included observation, documentation, and tests. The validation results from material experts showed a feasibility of 98%, indicating it was very feasible. Similarly, the validation results from media experts showed a feasibility of 88.3%, also indicating it was very feasible. These results indicated that the SURIA media was very suitable for use in learning. The effectiveness test, using the Pre-Test–Post-Test Non-Equivalent Control Group Design, showed that there was a significant increase in Sundanese vocabulary in children who used this media. SURIA media had been proven to improve cognitive and linguistic aspects, as seen from the results of the Paired Sample T-test, namely a sig value of 0.000 <0.05, which meant there was a significant difference before and after using SURIA media, showing that SURIA media was effective in improving the Sundanese vocabulary skills of early childhood children. In addition, SURIA media also fostered children's interest and love for regional languages. Therefore, this media was considered an innovative alternative in preserving Sundanese from an early age.